Structural difference analysis of gut microbiota in different bone mass populations and relevant probiotic (lactobacilli) supplementation strategies - Jiani Pan; Pingping Yin; Leilei Yu; Heng Zhang; Chengcheng Zhang; Jianxin Zhao; Fengwei Tian; Qixiao Zhai (Food Frontiers)
Abstract Disruption of the bone metabolic balance with advancing age leads to an escalating prevalence of bone‐related diseases, significantly compromising individuals’ quality of life. The gut microbiota actively participates in the regulation of bone metabolism, and perturbations in the gut microbiota can exacerbate bone diseases by compromising gut barrier integrity. Determining the microbial taxa involved in bone loss could offer valuable insights into the development of alternative therapies and nutritional interventions for disease management. Therefore, based on metagenomic and 16S ribosomal RNA data, this study analyzed the gut microbiota structure of 488 individuals with different bone masses (NC, normal; ON, osteopenia; OP, osteoporosis) to identify significant associations between the gut microbiota and bone loss. The results showed that at the genus and species levels, the microbiota diversity of the ON population increased, whereas that of the OP population decreased. Bacteroides were significantly enriched in the OP population, whereas the beneficial bacteria Bifidobacterium, Akkermansia, and lactobacilli decreased. Subsequent analyses revealed no significant variation in different bone populations in terms of Bifidobacterium levels, whereas lactobacilli exhibited diverse responses across distinct bone populations. The administration of lactobacilli effectively enhanced lumbar spine bone mineral density and modulated the gut microbiota structure in a population with unhealthy bone mass. This study contributes to the validation of the association between the gut microbiota and bone mass, enhances our understanding of the potential impact of probiotics (lactobacilli) on bone mass, and establishes a robust scientific basis for the application of probiotics in the regulation of bone mass.